Scoring and hedonic tests on herbal drinks with a combination of horse whip leaves (Stachytarpheta jamaicensis (L) vahl) and fresh white ginger (Zingiber officinale) - Nugrahani, Rizki; Yuniartini, Ni Luh Putu Sherly (Universitas Muhammadiyah Mataram, 2023)
Functional drinks have a meaning when the drink is consumed it will have a positive effect on the health of the body because it contains nutritional and non-nutritional elements.In line with the condition of the world that has just been attacked by the covid 19 virus, many people are currently turning to consuming concocted herbal drinks to help increase body immunity. One type of plant that is often used is ginger rhizome and horse whip leaves. The purpose of this research is to formulate horse whip leaves and fresh white ginger rhizomes as herbal drinks to support functional food diversification. In this herbal drink making research using a one-factor Completely Randomised Design (CRD) method, namely a mixture of horse whip leaves and fresh white ginger whose treatment consists of P1 = Horse Whip Leaves 90%: Fresh White Ginger 10%, P2 = Horse Whip Leaf 70%: Fresh White Ginger 30%, P3 = Horse Whip Leaf 50%: Fresh White Ginger 50%, P4 = Horse Whip Leaf 30%: Fresh White Ginger 70% and P5 = Horse Whip Leaf 10%: Fresh White Ginger 90%. Data were analysed using analysis of variance (ANOVA) at the 5% level in Microsoft Excel and IBM SPSS Statistics 25.0 applications and if significantly different data are obtained, further tests will be carried out using Honest Real Differences (5%). It was found that the combination of horse whip leaves and fresh white ginger on the herbal drink produced did not have a significant effect on the organoleptic characteristics of aroma and taste scoring tests but had a significant effect on colour parameters. For the organoleptic quality parameters of herbal drinks, it is known that the treatment has been produced in the scoring test with the highest value of colour in treatment P1 (yellow), aroma in treatment P2 (ginger-scented) and taste in treatment P3 (slightly warm ginger). The best treatment was obtained in the hedonic test with colour, aroma and taste parameters by treatment P5 (Horse Whip Leaf 10%: Fresh White Ginger 90%) with the criteria of liking.